Results from the Data & Democracy initiative to enhance community-based organization data and research capacity. - Carroll-Scott, Amy; Toy, Peggy; Wyn, Roberta; Zane, Jazmin I; Wallace, Steven P (American journal of public health, 2012)
In an era of community-based participatory research and increased expectations for evidence-based practice, we evaluated an initiative designed to increase community-based organizations' data and research capacity through a 3-day train-the-trainer course on community health assessments.
Keywords: Capacity Building; Community-Based Participatory Research; Educational Measurement; Humans; Los Angeles; Professional Competence; Self Efficacy; Teaching